Economic Analysis of Critical Distance Based on Frequency in Low Frequency AC for Offshore Wind Farms - Byeonghyeon An; Jeongsik Oh; Taesik Park (IEEE Access)
This paper presents a frequency-dependent cost analysis model for optimizing the economic performance of Low-Frequency AC (LFAC) transmission systems for offshore wind integration. Unlike previous studies that assumed fixed frequencies (e.g., 16.7 Hz or 20 Hz), the proposed model evaluates how variations in frequency affect the cost of key components, including transformers, offshore platforms, and submarine cables. By modeling the cost of the total system as a function of frequency, transmission capacity, and distance, the system’s optimal operating frequency is identified under various conditions. In addition, LFAC, High-Voltage AC (HVAC), and High-Voltage DC (HVDC) systems are compared based on the concept of economic critical distance, which defines the boundary between the most economically favorable transmission technologies depending on distance and capacity conditions. The results show that HVAC is the most cost-effective solution for short transmission distances, LFAC is optimal for medium-range transmission, and HVDC is favorable for long-distance applications. Notably, LFAC outperforms HVDC when cable multiplication is avoided, confirming its competitiveness in midrange scenarios. These findings demonstrate that considering frequency as a design parameter significantly improves the cost efficiency of LFAC systems and should be reflected in the early-stage planning of offshore transmission system design.